Recent rift-related volcanism in Afar, Ethiopia - Ferguson, David J.; Barnie, Talfan D.; Pyle, David M.; Oppenheimer, Clive; Yirgu, Gezahegn; Lewi, Elias; Kidane, Tesfaye; Carn, Simon; Hamling, Ian (Earth and Planetary Science Letters, 2010)
Rift zones are the most common magmatic environment on Earth. However opportunities to observe active rifting are rare, and consequently the volcanological characteristics of rift systems are not well understood. An ongoing phase of magmatic rifting along a section of the Red Sea system in Afar, Ethiopia, presents an exceptional opportunity to constrain relationships between volcanism and crustal growth. Here, by integrating analyses of satellite images (i.e. MODIS, OMI, ASTER, and ALI) with field observations, we characterise two recent (August 2007 and June 2009) basaltic fissure eruptions in Afar and evaluate the role and significance of volcanism in the rifting process. Both events were brief (36-72h) and erupted 4.4-18×106m3 of lava from a fissure system 4-6.5km in length. Data from the spaceborne Ozone Monitoring Instrument (OMI) suggests total SO2 emissions for each eruption of 26±5kt (2007) and 34±7kt (2009), consistent with complete degassing of the erupted magma volumes. Using geodetic models for the intrusive activity in Afar we estimate the partitioning of magma between intrusive and extrusive components, up to July 2009, to be ~180:1. Comparing the first-order volcanic characteristics and the intrusive-extrusive volume balance for the Afar volcanism with data from the 1975-1984 Krafla rifting cycle (Iceland) suggests that the volcanic flux in Afar will rise significantly over the next few years as the stresses are increasingly relieved by dyking, and subsequent dykes are able to propagate more easily to the surface. As a consequence, basaltic fissure eruptions in this section of the Afar rift will become of increasing large magnitude as the rifting event matures over the next 5-10yr. Using available models of magmatic rifting we forecast the likely size and location of future eruptions in Afar. © 2010 Elsevier B.V.